EDITORIAL - Calle Martínez, Cristina; Madarova, Slavka; García Laborda , Jesús (Encuentro Journal, 2020)
Six articles published in this issue cover three main areas of interest: first, language learning and methodology are in focus; next, new approaches to improve English writing and oral skills. Finally, the last section concentrates on the attitudes and perception of teachers about the English lessons in foreign education systems and on translation studies.